2014
DOI: 10.1039/c4ra07570f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of mixed phase anatase TiO2 and sodium-doped TiO2(B) thin films by low pressure chemical vapour deposition (LPCVD)

Abstract: TiO 2 thin films were synthesized using Low Pressure Chemical Vapour Deposition (LPCVD) onto glass substrates. Titanium isopropoxide (TTIP) and N 2 gas were used as the precursor and carrier gas respectively. The effects of reaction temperature, carrier gas flow rate and deposited area were studied. SEM, TEM, powder XRD and UV-Vis and Raman spectroscopy were employed to characterize the phase and morphology of the synthesized materials. The results show that a dual phase (sodium-doped TiO 2 (B) and anatase) na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 44 publications
(58 reference statements)
5
28
0
Order By: Relevance
“…It can be observed that the absorption thresholds at 400 nm for R5 samples are slightly blue-shifted compared to that of R15 one and the degree of blue shift slightly increases with the amount of rutile content. The integral band gap energy agrees with the full width at half maximum (FWHM) shown in Figure 2 XRD pattern, meaning the smaller FWHM has the better conductivity, and proposes narrow band gap energy [ 20 , 21 ].…”
Section: Resultssupporting
confidence: 60%
“…It can be observed that the absorption thresholds at 400 nm for R5 samples are slightly blue-shifted compared to that of R15 one and the degree of blue shift slightly increases with the amount of rutile content. The integral band gap energy agrees with the full width at half maximum (FWHM) shown in Figure 2 XRD pattern, meaning the smaller FWHM has the better conductivity, and proposes narrow band gap energy [ 20 , 21 ].…”
Section: Resultssupporting
confidence: 60%
“…One common thread between these recipes is the use of some ionic complexing agent (Na + , C 2 O 4 2− , or Cl − ) to favor the structural selection of brookite in large quantities. However, vapour deposition processes inspired by the proposed growth mechanisms do not consistently lead to the same results 26 .…”
Section: Introductionmentioning
confidence: 93%
“…3b shows the HRTEM images of the ZnO-TiO 2 composite NFs at the surface that have two different lattice fringes with spacings of 0.350 nm and 0.274 nm, which represent the (101) plane of the anatase TiO 2 and the (100) plane of the hexagonal ZnO, which correlated well with the XRD results. 25,26 However, the HRTEM images of the NFs that were annealed at 800°C revealed the uniform distribution of fringes with a lattice spacing of 0.270 nm, which clearly represents the ternary form of ZnTiO 3 at the surface (Fig. 3e).…”
Section: Resultsmentioning
confidence: 98%